Hak dan Kewajiban Suami Isteri dalam Rumah Tangga Perspektif Hukum Islam - Andini, Dwi (Maliki Interdisciplinary Journal, 2024)
The rights and obligations of husbands and wives are very important in building a harmonious, loving and prosperous household. From an Islamic perspective, marriage is not just a physical relationship, but is also a sacred agreement where both parties are responsible for fulfilling their respective rights and obligations. Islam provides clear guidelines regarding these rights and responsibilities to ensure balance and justice in the family. For example, in Surah al-Nisa verse 34, men are appointed as head of the family and are responsible for providing support and protection, while women are obliged to maintain honor as long as this is consistent and are expected to show submission to their husbands, as long as this is in accordance with the Shari'ah.